2020
DOI: 10.1016/j.amsu.2020.11.076
|View full text |Cite
|
Sign up to set email alerts
|

Complete diaphysis resorption of the femur: A case report in a metastatic papillary thyroid cancer

Abstract: Introduction Although differentiated thyroid cancers generally have a good prognosis, a small proportion of patients will have recurrent or progressive disease. Bone resorption due to thyroid cancer can cause significant challenges in the clinical management and rehabilitation. Presented case Nearly total femur resorption was found as a first presentation in a patient with thyroid cancer. The patient complained about chronic pain in her left thigh that had progressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…A papillary thyroid malignancy was post-operatively confirmed. The patient further underwent 131 I radioiodine therapy (200 mCi), local radiotherapy, and monthly zoledronate therapy for bone involvement [ 33 ].…”
Section: Results: Sternal Metastases—a Multidisciplinary Perspective ...mentioning
confidence: 99%
“…A papillary thyroid malignancy was post-operatively confirmed. The patient further underwent 131 I radioiodine therapy (200 mCi), local radiotherapy, and monthly zoledronate therapy for bone involvement [ 33 ].…”
Section: Results: Sternal Metastases—a Multidisciplinary Perspective ...mentioning
confidence: 99%
“…For instance, DLBCL of the mandibular bone was incidentally found to be associated with papillary thyroid carcinoma in a case report [ 24 ]. Suwardjo et al reported the presence of papillary thyroid cancer with NOF fracture [ 25 ]. Evans et al reported a case of primary thyroid lymphoma with bone marrow infiltration at presentation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Papillary thyroid carcinoma has been considered as indolent cancer with lower propensity to metastasize to distant organs. In circumstances of delayed diagnosis or inadequate initial detection and treatment, however, we have reported some cases of papillary thyroid cancer with large bone resorption [ 10 ] and gross extrathyroidal extension [ 11 ]. Several factors including large tumor size, lymphovascular invasion, and certain aggressive variants are associated with distant metastases [ 2 , 12 ].…”
Section: Clinical Discussionmentioning
confidence: 99%